ARCIC on Mary: An Historical Consideration of the Use of Early Church Evidence in the Seattle Statement - Painter, John (Journal of Anglican studies, 2006)
The ARCIC Statement on Mary features an underlying agreement on Mary as a basis for recommending that Anglicans accept the two Marian dogmas of the Immaculate Conception and the Assumption as matters of faith. In outlining the case it becomes clear that the place of Scripture, as expressed in Article 6 of the Thirty Nine Articles, is different in the two Communions. The two Marian dogmas shift the focus of the underlying agreement so that Mary becomes more aligned with Jesus than believers. Mary's sinlessness, which is the focus of the dogma of Immaculate conception, apparently involves her continuing virginity. Though perpetual virginity is assumed in the creeds and the Book of Common Prayer, it is not explicitly connected with Mary's purity or sinlessness. This move is consistent with the place of virginity and celibacy in the Roman Catholic Church. It is a serious difference from the Anglican position. In addition, ecumenical research brings into question the view that Mary remained ever a virgin recognizing children born to Joseph and Mary. Historically and exegetically the mother and brothers of Jesus are seen as believers and followers of Jesus.